Dampak Kebijakan Alih Daya Undang-Undang Cipta Kerja terhadap Tenaga Kerja di Indonesia - Suryanto, Tri; Santoso, Imam Budi (Wajah Hukum, 2024)
The presence of the Job Creation Law has backfired on the current employment system in Indonesia. The reason is, the presence of the Job Creation Law has become a worry for most Indonesian people, especially workers. In the Job Creation Law in the employment cluster, the public considers that there are many articles that are considered to have the potential to violate workers' rights, such as the regulation of outsourcing as regulated in the previous law, namely the Employment Law. In the Manpower Law, only certain jobs that are not included in the main activities or production processes may be outsourced, except for supporting functions. However, in the Job Creation Law, there are no restrictions on the types of work that can be done by outsourced workers. This happened because Articles 64 and 65 were deleted, as well as modifications to Article 66 in the Manpower Law. Thus, the new regulations allow for an expansion in the scope of work that can be outsourced, including the elimination of permanent job security, thereby allowing all types of work to be carried out through outsourcing.